2006
DOI: 10.1111/j.1548-2456.2006.tb00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Institution Building: The PT and Participatory Budgeting in Rio Grande do Sul

Abstract: In the late 1990s, the Workers' Party (PT) government of the Brazilian state of Rio Grande do Sul introduced participatory budgeting, a process in which citizens establish annual investment priorities in public assemblies. This innovation was one of several attempts by incumbent parties to structure political conflict using budget institutions. The character of participatory budgeting is most evident in its policymaking processes and policy outcomes. The process circumvented legislative arenas where opponents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Other analysts of institutional design have also found that the operations and design of PDPs are sites, and also represent outcomes, of competition between actors in representative institutions (Goldfrank 2007;Goldfrank and Schneider 2007). Finally, the problems that the SCA faced interacting with the organizational structure and political and policy cycles of government are in part a design fault, and also attributable to contextual variations such as electoral outcomes or the opening of policy windows.…”
Section: Structural Constraintsmentioning
confidence: 99%
“…Other analysts of institutional design have also found that the operations and design of PDPs are sites, and also represent outcomes, of competition between actors in representative institutions (Goldfrank 2007;Goldfrank and Schneider 2007). Finally, the problems that the SCA faced interacting with the organizational structure and political and policy cycles of government are in part a design fault, and also attributable to contextual variations such as electoral outcomes or the opening of policy windows.…”
Section: Structural Constraintsmentioning
confidence: 99%
“…But it also offers opportunities for manipulation (see Abers, ; Wampler, ). PB plays a strategic part in partisan power struggles, and therefore does not have empowerment as its primary political goal (Goldfrank and Schneider, ). Wampler's comparative study of eight Brazilian PBs, the most ambitious study to date of cooptation and non‐cooptation in PB, suggests that outcomes depend on participants' capacities of combining cooperative and contentious strategies to gain access to a field of interaction with government officials but also distance themselves from policies that they do not agree with.…”
Section: The Challenge Of Cooptation In Participatory Budgetingmentioning
confidence: 99%
“…Yet experiments to scale up PB to the state level in Rio Grande do Sul, of which Porto Alegre is the capital, have failed (Goldfrank and Schneider 2006 ). There is no ideal city size for participatory experiments (where people know each other personally, as Aristotle suggested).…”
Section: Geographical Refl Ectionsmentioning
confidence: 99%